Wireless spinal cord stimulation technology for the treatment of neuropathic pain: a single-center experience - Ahmadi, Rezvan; Hajiabadi, Mohammad Mehdi; Unterberg, Andreas; Geist, Christiane; Campos, Benito (Neuromodulation, 2021)
Objectives A new wireless spinal cord stimulation (SCS) technology, which was introduced in recent years, promises minimal invasive SCS as well as additional advantages such as a wide range of stimulation paradigms and 3-T magnetic resonance imaging (MRI) conditionality. Materials and Methods We prospectively evaluated 12 patients suffering from therapy-resistant neuropathic pain, who were implanted with a wireless SCS system from 2017 to 2019. Potential issues pertaining to handling and usability of the SCS device were evaluated from a patients' as well as from a surgeon's perspective. Results Mean follow-up was 228.0 days (95% CI, 20.0-518.0 days). We did not record any handling issues nor did we record any relevant local discomfort associated with the implanted SCS device. N = 3/12 patients reported discomfort from wearing the SCS antenna and one patient complained about a short battery life of the controller device. There were no reported incidents during 3-T MRI studies. After an average test period of 51.7 days (95% CI, 11.0-104.0 days), N = 9/12 patients (75%) had reached pain relief of 50% or more with an average pain relief (responders and partial responders) of 67.4% (95% CI, 50.0%-85.0%). On average, patients tested 2.2 different stimulation paradigms, with frequencies ranging from 60 Hz to 10 kHz, but there was no preferred stimulation paradigm. Conclusions Minimal invasive implantation of wireless SCS systems was feasible and safe. The device offered a broader range of stimulation paradigms compared to conventional SCS devices, an allowed for a prolonged testing phase and continuous adjustment of SCS programs.